How to obtain the maximum benefit from scientific research funds: the example of Costa Rica (achievements and challenges, FEES 2006-2016) (UNED Research Journal, 2019)
Introduction: Costa Rica is the country with the most developed scientific community in Central America. In 2005, Costa Rican public universities, coordinated by a Council of Public Universities (CONARE), decided that, instead of working in isolation, they would pool resources. These financed joint research to solve environmental problems and support groups in disadvantage, like women and minorities. Objective: to examine the results after the first ten years of the program with emphasis on who received the funds and what products were obtained. Methods: we surveyed project coordinators and obtained replies from about half of them (i.e. the coordinators of 71 projects answered). Results: We found that 60% of research funds benefited disadvantaged populations (i.e. those in coastal and border areas) and that 54% of researchers who received funds were female. Survey projects produced 1388 scientific articles and 883 practical products, such as community workshops and commercial start-ups (estimate: over 2700 articles and 1700 practical products for the whole set of projects). Conclusion: These projects have been highly productive, have benefited women and underserved communities, led to lasting collaboration among researchers from different institutions, and are an example for other small countries with limited research funds.
Keywords: fund distribution; research and development; women in science; science for underserved communities; academic cooperation in the tropics; impact of science; CONARE.